STUDI PERENCANAAN PROYEK MODERNISASI SALURAN IRIGASI DAERAH INDRAMAYU - Rein Algaven Rimbo; Robby Yussac Tallar (Journal of Smart Technology and Engineering, 2025)
Irrigation is an effort to obtain and distribute water to support agricultural activities including plantations, fields and rice fields. Irrigation work is one of the criteria that describes the management of irrigation systems. Irrigation is divided into four parts, namely, Gravity Irrigation, Underground Irrigation, Sprinkle Irrigation, and Drip Irrigation. In this plan, it is located in Kab. Cirebon and Indramayu, West Java Province, in this study I will plan secondary irrigation channels at predetermined locations. In this report we will discuss, calculating the amount of water discharge, calculating the cross-sectional area of the channel, calculating the height of the channel, calculating the width of the channel, planning the height and cross-sectional area of the channel, determining the height of the trapezium shaped channel, calculating the planned flow velocity, calculating the hydraulic circumference, calculating the radius. -hydraulic radius, and calculating the slope of the channel. Keywords: Irrigation, channels, discharge